2021
DOI: 10.1108/ijbm-12-2020-0612
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and consequences of Personal Financial Management Behavior: a systematic literature review and future research agenda

Abstract: PurposeThe purpose of this paper is to investigate the current state of research on Personal Financial Management Behavior (PFMB), with a prime focus on its antecedents and the consequences. By analyzing the research trends, methods, determinants and outcomes, the PFMB literature is synthesized, and agenda for future research is suggested. A framework is presented that portrays PFMB's antecedents and consequences and further specification of the mediation and moderation linkages.Design/methodology/approachThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 151 publications
(162 reference statements)
2
85
0
4
Order By: Relevance
“…That is to say, the aspects of sustainable finance did not take center stage in the investigation of those articles, resulting in their removal. This led to a final corpus of 936 articles for review, which was confirmed following a random cross-check using other databases such as Google Scholar and publishers website such as Elsevier, Emerald, Sage, Springer, and Taylor and Francis to avoid unintended exclusion of relevant studies in the field (Goyal et al, 2021 ; Harari et al, 2020 ; Lim et al, 2021 ).…”
Section: Methodsmentioning
confidence: 96%
“…That is to say, the aspects of sustainable finance did not take center stage in the investigation of those articles, resulting in their removal. This led to a final corpus of 936 articles for review, which was confirmed following a random cross-check using other databases such as Google Scholar and publishers website such as Elsevier, Emerald, Sage, Springer, and Taylor and Francis to avoid unintended exclusion of relevant studies in the field (Goyal et al, 2021 ; Harari et al, 2020 ; Lim et al, 2021 ).…”
Section: Methodsmentioning
confidence: 96%
“…In doing so, this study extends the insights from domain-specific reviews within the larger domain of bank marketing, such as Molina-Collado et al. 's (2021) bibliometric review on consumer financial services, Zainuldin and Lui's (2021) bibliometric review of corporate social responsibility in the banking industry and Goyal et al. 's (2021) systematic literature review on personal financial management behavior.…”
Section: Introductionmentioning
confidence: 66%
“… 33 Emotions, genetics, heredity, gender, biasness, and culture were first deemed ineffectual in financial decision-making by the researchers. 16 Researchers have learned throughout time that, despite having adequate models to build future cash flow projections, anticipated needed rates of return, compute discounted cash flows, and develop capital expenditure (“capex”) presentations, they are unable to do so. These models are critical; no one can deny that, but researchers are unable to account for emotions and other such aspects while making financial decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Emotions have a surprising amount of predictability when it comes to financial decisions. 4 , 6 , 16 We have a tendency to be overconfident in our knowledge and judgments, to extrapolate recent patterns while disregarding the past, and to fail to accept defeats graciously by clinging to our losers for far too long, among other things. Even the most seasoned investors are vulnerable.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation